Analisis Berpikir Relasional Siswa Climber dalam Memecahkan Masalah Matematika (Jurnal Inovasi Pendidikan Matematika (JIPM), 2023)
This study aims to determine the relational thinking ability of climber students in solving mathematical problems. This type of research is a qualitative research with a phenomenological approach. Taking the subject with a purposive technique. The research subjects were students of class VIII of junior high school who had the adversity quotient intelligence of the climber type. Data collection techniques used are questionnaires, tests, interviews, documentation, and field notes. The analysis technique used is data reduction, data presentation, and conclusion drawing. The results showed that climber students only carried out relational thinking activities at the stage of implementing the plan. At this stage, climber students are able to connect the information provided with previous knowledge, namely utilizing knowledge about the LCM of a number to change the equation into an equivalent form in order to be able to perform the SPLDV solution method. In addition, climber students build relationships using mathematical properties, namely solving SPLDV using mixed methods (elimination and substitution) to find the value of a variable by performing several mathematical operations involving the use of inverse properties in multiplication and inverse properties in addition.